Long‐term follow‐up of a single dose of fluralaner in nine dogs with demodicosis. Issue 4 (8th April 2021) - Hoshino, Tomoya; Akita, Takahiro; Sugeno, Akihiro; Okamura, Taku; Machida, Yuko; Nagata, Masahiko
Abstract : Background: Long‐term follow‐up of oral fluralaner for canine demodicosis has not been demonstrated. Objectives: A multicentre prospective open trial for the efficacy of oral fluralaner for the long‐term (>12 month) management of canine demodicosis. Animals: Client‐owned dogs diagnosed with demodicosis at nine veterinary clinics. Methods and materials: A single fluralaner dose was administered orally. Although shampoo was allowed to treat secondary pyoderma, no other medication or shampoo was allowed, except for medication for possible underlying disorders. Each dog underwent a thorough parasitological and dermatological assessment monthly for three months and was followed up for >12 months. Results: Twenty‐six dogs were enrolled. Their ages ranged from three months to 16 years. The cases were nine juvenile and 17 adult onsets; and 18 generalised and eight localised forms. Fluralaner administration resulted in 100% eradication of mites and complete resolution of all skin lesions at three months. Seventeen dogs were excluded from the one year follow‐up evaluation as they had required a second dose of isoxazoline or died from causes unrelated to the fluralaner treatment. In the remaining nine cases, no relapse was observed in any of the dogs (six adult and three juvenile onsets; six generalised and three localised forms). Four dogs were monitored for over one year, one dog for over two years, and four dogs for three years. Conclusions and clinical relevance: The results indicated that a single dose of fluralaner could effectively deliver a long‐term cure when combined with managing underling conditions. Abstract : Background – Long‐term follow‐up of oral fluralaner for canine demodicosis has not been demonstrated. Objectives – A multicentre prospective open trial for the efficacy of oral fluralaner for the long‐term (>12 month) management of canine demodicosis. Conclusions and clinical relevance – The results indicated that a single dose of fluralaner could effectively deliver a long‐term cure when combined with managing underling conditions. Résumé: Contexte: Le suivi au long cours de flurolaner oral pour la démodécie canine n'a pas été réalisé. Objectifs: Une étude ouverte multicentrique prospective pour l'efficacité du flurolaner oral au long cours (>12 mois) dans la gestion de la démodécie canine. Sujets: Des chiens de propriétaires diagnostiquées avec démodécie dans neufs cliniques vétérinaires. Matériels et methods: Une dose unique de flurolaner a été administrée oralement. Bien que le shampooing soit prescrit pour traiter la pyodermite bactérienne, aucun autre traitement n'a été administré à l'exception de maladie sous‐jacentes possibles. Chaque chien a eu une évaluation parasitaire et dermatologique mensuelle pendant trois mois et a été suivi pendant plus de 12 mois. Résultats: Vingt six chiens ont été inclus. Leur âge était compris entre trois mois et 16 ans. Neufs cas étaient juvéniles et 17 étaient adultes ; 18 étaient généralisés et huit, localisés. L'administration de fluralaner a permis une éradication de 100% des acariens et une résolution complète de toutes les lésions cutanées à trois mois. Dix sept chiens ont été exclus de la période suivi de 12 mois lorsqu'ils ont du recevoir une autre dose d'isoxazoline ou qu'ils sont morts de causes non liées au fluralaner. Dans les neufs cas restants, aucune récidive n'a été observée (six adultes et trois juvéniles ; six formes généralisées et trois formes localisées). Quatre chiens ont été suivis pendant un an, un chien pendant deux ans et quatre chiens pendant trois ans. Conclusions et importance Clinique: Les résultats indiquent qu'une seule dose de fluralaner peut permettre une guérison efficace au long cours lorsqu'associé à un traitement de la cause sous jacente. Resumen: Introducción: no se ha investigado el seguimiento a largo plazo de fluralaner oral para la demodicosis canina. Objetivos: Un estudio abierto, prospectivo, multicéntrico de la eficacia del fluralaner oral para el tratamiento a largo plazo (>12 meses) de la demodicosis canina. Animales: perros de propietarios privados diagnosticados con demodicosis en nueve clínicas veterinarias. Métodos y materiales: se administró una sola dosis de fluralaner por vía oral. Aunque se permitió el champú para tratar la pioderma secundaria, no se permitió ningún otro medicamento o champú, excepto los medicamentos para posibles trastornos subyacentes. Cada perro se sometió a una evaluación parasitológica y dermatológica exhaustiva mensualmente durante tres meses y se realizó un seguimiento durante> 12 meses. Resultados: Se inscribieron 26 perros. Sus edades oscilaron entre los tres meses y los 16 años. Los casos fueron nueve casos juveniles y 17 adultos; y 18 formas generalizadas y ocho localizadas. La administración de Fluralaner resultó en la erradicación del 100% de los ácaros y la resolución completa de todas las lesiones cutáneas a los tres meses. Diecisiete perros fueron excluidos del seguimiento de un año porque habían requerido una segunda dosis de isoxazolina o habían muerto por causas no relacionadas con el tratamiento con fluralaner. En los nueve casos restantes, no se observó recaída en ninguno de los perros (seis episodios adultos y tres juveniles; seis formas generalizadas y tres localizadas). Se siguieron cuatro perros durante más de un año, un perro durante más de dos años y cuatro perros durante tres años. Conclusiones y relevancia clínica: los resultados indicaron que una sola dosis de fluralaner podría proporcionar una cura eficaz a largo plazo cuando se combina con el manejo de las condiciones subyacentes. Zusammenfassung: Hintergrund: Bisher wurde kein langfristiger Follow‐Up einer Demodikose Behandlung mit Fluralaner demonstriert. Ziele: Eine Multicenter prospektive offene Studie zur Wirksamkeit von Fluralaner per os zur Langzeitbehandlung (>12 Monate) der caninen Demodikose. Tiere: Es wurden Hunde in Privatbesitz, die in neun veterinärmedizinischen Kliniken mit einer Demodikose diagnostiziert worden waren, in die Studie aufgenommen. Methoden und Materialien: Es wurde eine einzelne Dosis Fluralaner per os verabreicht. Obwohl Shampoo zur Behandlung einer sekundären Pyodermie eingesetzt werden dürfte, waren keine anderen Medikamente oder Shampoo erlaubt, außer einer Medikation für eventuell zugrundeliegende Erkrankungen. Bei jedem Hund wurde monatlich drei Monate lang eine gründliche parasitologische und dermatologische Untersuchung durchgeführt und es bestand ein Follow‐Up für >12 Monate. Ergebnisse: Es wurden sechsundzwanzig Hunde in die Studie aufgenommen. Das Alter reichte von drei Monaten bis zu 16 Jahren. Es handelte sich um neun Fälle mit juvenilem und 17 Fälle mit adultem Auftreten; es waren 18 generalisierte und acht lokalisierte Formen vertreten. Die Verabreichung von Fluralaner ergab nach drei Monaten ein 100%iges Auslöschen der Milben und eine völlige Abheilung der Hautveränderungen. Siebzehn Hunde wurden vom Follow‐Up nach einem Jahr ausgeschlossen, da sie eine zweite Isoxazolid Dosis benötigten oder aus anderen (nicht mit Fluralaner im Zusammenhang stehenden) Gründen verstorben waren. Bei den verbleibenden neun Fällen wurde bei keinem der Hunde (sechs adulte und drei juvenile Formen; sechs generalisierte und drei lokalisierte Formen) ein Rückfall beobachtet. Vier Hunde wurden ein Jahr lang weiter beobachtet, ein Hund zwei Jahre lang und vier Hunde für drei Jahre. Schlussfolgerungen und klinische Bedeutung: Diese Ergebnisse zeigen, dass eine einzige Dosis Fluralaner effektiv eine Langzeitheilung ermöglichte, wenn es mit dem Management der zugrundeliegenden Erkrankungen kombiniert wurde. 要約: 背景: 犬ニキビダニ症に対するフルララネル経口投与の長期追跡調査は実証されていない。 目的: 本研究の目的は、犬の皮膚病の長期 (12ヶ月以上) 管理における経口フルララネルの有効性を多施設共同前向きオープン試験で検討することであった。 供試動物: 9つの動物病院でニキビダニ症と診断されたクライアント所有犬。 材料と方法: フルララネルを1回経口投与した。シャンプーは二次的に生じた膿皮症治療のため許可されていたが、基礎疾患の可能性がある場合の投薬を除いて、他の薬やシャンプーは許可されなかった。各犬は3ヶ月間、毎月寄生虫学的および皮膚科学的評価を徹底的に受け、12ヶ月以上のフォローアップを実施した。 結果: 26頭の犬が登録された。年齢は3ヶ月から16歳までであった。症例の内訳は、若齢発症が9例、成犬発症が17例、汎発型が18例、局所型が8例であった。フルララネル投薬により、3ヵ月後にはダニは100%駆除され、すべての皮膚病変は完全に消失した。17頭の犬(2回目のイソキサゾリン投与が必要である犬や、フルララネル投薬とは無関係の原因で死亡した犬) は、1年後の追跡評価から除外された。残りの9頭は、どの犬にも再発は見られなかった (成犬発症6例、若齢発症3例、汎発型6例、局所型3例) 。4頭の犬は1年以上、1頭は2年以上、4頭は3年以上経過を観察した。 結論と臨床的妥当性: この結果は、フルララネルの単回投与が、背景疾患の管理と組み合わせることで、効果的に長期的な治癒をもたらすことを示している。 Abstract : 背景: 尚无口服氟雷拉纳治疗犬蠕形螨病的长期随访记录。 目的: 一项评价口服氟雷拉纳长期 (> 12个月) 治疗犬蠕形螨病疗效的多中心前瞻性开放试验。 动物: 在9家兽医诊所诊断为蠕形螨病的私家犬。 方法和材料: 氟雷拉纳口服给药一次。虽然允许使用香波治疗继发性脓皮病, 但除治疗可能的潜在疾病的药物外, 不允许使用其他药物或香波。每只犬每月接受一次全面的寄生虫学和皮肤病学评估, 持续3个月, 并随访 > 12个月。 结果: 入组26只犬。其年龄3个月 16岁。这些病例为9例幼年和17例成年发病; 18例全身型和8例局部型。氟雷拉纳给药可100%根除螨虫, 3个月时所有皮肤病变完全消退。17只犬从1年随访评价中排除, 因为其需要第二次异噁唑啉给药或死于与氟雷拉纳治疗无关的原因。在其余9例病例中, 均未观察到复发(6例成年和3例幼年发病;6例全身型和3例局部型) 。4只犬监测1年以上, 1只犬监测2年以上, 4只犬监测3年。 结论和临床相关性: 结果表明, 如果同时管理潜在疾病, 口服一次氟雷拉纳可有效提供长期治愈。 Resumo: Contexto: Não foi ainda demonstrado o acompanhamento de longo prazo do uso de fluralaner por via oral para cães com demodiciose. Objetivos: Um ensaio clínico prospectivo multicêntrico para avaliar a eficácia do fluralaner oral no manejo de demodiciose canina em longo prazo (> 12 meses). Animais: Cães de proprietários diagnosticados com demodiciose em nove clínicas veterinárias. Métodos e materiais: Uma dose única de fluralaner foi administrada oralmente. Apesar de shampoo ter sido permitido para tratar piodermite secundária, nenhuma outra medicação ou shampoo foi permitido, exceto medicações para possíveis distúrbios subjacentes. Cada cão foi submetido a uma avaliação dermatológica e parasitológica completa mensalmente por três meses e foi acompanhado por > 12 meses. Resultados: Vinte e seis cães foram incluídos. Suas idades variaram entre três meses a dezesseis anos. Havia nove cães com demodiciose juvenil e 17 de fase adulta; e 18 apresentaram a forma generalizada e oito a localizada. A administração de fluralaner resultou na erradicação de 100% dos ácaros e resolução completa de todas as lesões cutâneas em três meses. Dezessete cães foram excluídos da reavaliação anual porque precisaram de mais uma dose de isoxazolina ou morreram por causas não relacionadas ao tratamento com fluralaner. Não foi observada recidiva em nenhum dos nove cães remanescentes (seis apresentando demodiciose de fase adulta e três a juvenil); seis com a forma generalizada e três localizada. Quatro cães foram monitorados por mais de um ano, um cão por mais de dois anos e quatro cães por mais de três anos. Conclusões e relevância clínica: Os resultados indicam que uma dose de fluralaner pode fornecer satisfatoriamente a cura a longo prazo quando associado com o tratamento das doenças de base.